Relationship and Interconversion Between Superhydrophilicity, Underwater Superoleophilicity, Underwater Superaerophilicity, Superhydrophobicity, Underwater Superoleophobicity, and Underwater Superaerophobicity: A Mini-Review - Yong, Jiale; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Chemistry, 2020)
Superwetting surfaces have received increasing attention because of their rich practical applications. Although various superwettabilities are independently achieved, the relationship between those superwettabilities is still not well clarified. In this mini-review, we show that superhydrophilicity, underwater superoleophilicity, underwater superaerophilicity, superhydrophobicity, underwater superoleophobicity, and underwater superaerophobicity can be obtained on a same structured surface by the combination of hierarchical surface microstructures and proper chemistry. The relationship and interconversion between the above-mentioned different superwettabilities are also well discussed. We believe that the current discussion and clarification of the relationship and interconversion between different superwettabilities has important significance in the design, fabrication, and applications of various superwetting materials.